2014
DOI: 10.5588/ijtld.13.0395
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in human immunodeficiency virus-infected children starting antiretroviral therapy in Côte d'Ivoire

Abstract: Ensuring clinician compliance with TB screening before ART and ensuring earlier ART initiation before children suffer from advanced HIV disease and nutritional compromise might reduce TB morbidity during ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…Similar studies conducted in Kenya [9, 38], Uganda and Zimbabwe [39], Tanzania [24], Cote D’Ivoire [40], and South Africa [21] were concordant with ours. A possible explanation was children might have had a non-symptomatic TB at the time of ART initiation.…”
Section: Discussionsupporting
confidence: 91%
“…Similar studies conducted in Kenya [9, 38], Uganda and Zimbabwe [39], Tanzania [24], Cote D’Ivoire [40], and South Africa [21] were concordant with ours. A possible explanation was children might have had a non-symptomatic TB at the time of ART initiation.…”
Section: Discussionsupporting
confidence: 91%
“…A study in children from Côte d'Ivoire similarly showed that HIV stage 3/4 was a risk factor for co-infection. 4 In our study, severe immunosuppression was an important risk factor for PTB-HIV co-infection. This finding is consistent with those of other studies in African children.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is consistent with those of other studies in African children. 4,5,23 Severe immunosuppression in TB-HIV co-infection has largely been attributed to CD4+ T-cell depletion. 24,25 Severe immunosuppression in children with HIV mono-infection or HIV-TB co-infection has been associated with poor clinical outcomes and increased mortality with or without ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…characteristics of the eligible studies are summarised in Table 1. Tuberculosis: Nine studies 15,[17][18][19][20]22,32,35 on TB were pooled to give an overall incidence rate estimate of (95% CI 30 -70) per 1,000 child-years at risk for tuberculosis based on a 4 random-effects model (I 2 = 99%; Figure 2). Subgroup analysis established change over time in 5 incidence rates when comparing studies conducted before and after 2011.…”
mentioning
confidence: 99%